The Experience of European Countries in Managing the Expenditures of Enterprises in the Agricultural Sector - Reznik, Andrii; Lavrynenko, Svitlana; Zeliska, Antonina; Mardus, Nataliia; Samborska, Oksana (My University, 2022)
Ensuring the efficient development and functioning of agricultural enterprises depends on the rationally formed optimal level of costs for the implementation of economic activities, particularly for the production of agricultural products. This article aims to describe methodological principles of cost management of agricultural enterprises based on the European Union countries using determination of interconnection between total costs of agricultural enterprises and indicators of the value of agricultural products manufactured by them. Methods: theoretical analysis, abstraction, induction, deduction, tabular and graphical presentation, description, comparison, comparison, and generalization. Results: It was found that the disclosure of methodological principles of cost management of agricultural enterprises should be carried out by identifying the relationship between the total costs of agrarian enterprises and indicators of the cost of agricultural products produced by them using correlation analysis. As a result of correlation analysis, we established direct and reversed very high, high, medium, moderate, and weak correlations between the indicator of total costs of agricultural enterprises and the indicator of the cost of grain growing, index of production cost of industrial crops and the index of the cost of forage crops production according to the surveyed countries of the European Union. It was found that with very high and high intensity of interconnection between the analyzed variables. The increase in the indicator of total costs directly affects the growth of the cost of growing crops by agricultural enterprises in Austria, Belgium, Bulgaria, Croatia, Cyprus, Estonia, Latvia, the Netherlands, and Romania. The growth in the indicator of total costs directly affects the growth of the production cost of industrial crops by agricultural enterprises of Denmark, Estonia, Greece, Latvia, and Portugal and the increase in the indicator of total costs directly affects the increase in the cost of growing forage crops by agricultural enterprises of Belgium, Croatia, Cyprus, Estonia, Ireland, the Netherlands, Romania, Slovenia, Spain, and Sweden. The prospect of the following research is to disclose the methodological principles of cost management of agricultural enterprises on the application of the United States of America.
Keywords: agricultural business; production of agricultural products; gross value added; correlation analysis